Soil Organic Matter and Soil Organic Carbon in Barito Delta - Novi Rahmawati (Pusat Kajian Berkelanjutan UIN Sulthan Thaha Saifuddin Jambi, 2023)
Soil organic matter and soil organic carbon is essential indication of soil carbon stock in terrestrial ecosystem particularly in peatland. Spatial distribution of soil organic carbon and soil organic matter is primary assessment to predict future soil condition under climate change traits. Barito Delta is one of peatland areas in Kalimantan Island that experiences urban expansion. It is necessary to assess distribution of soil organic carbon and soil organic matter to define the potential traits of urbanization and climate change to carbon stock condition in this delta. Therefore, the aim of this research is to analyze the distribution of soil organic matter and soil organic carbon in Barito Delta. Fieldwork measurement is performed to take sample of soil organic matter for each layer within 5 m soil depth. Inverse distance weighting interpolation is used to determine the spatial distribution of soil organic matter (SOM) and soil organic carbon (SOC) applying in R software. The value of SOM and SOC decrease along the increase of soil depth so that the largest percentage of SOM and SOC is in the first layer. Large value of SOM and SOC are mostly in the southern part of Barito Delta since it is bordered with sea water and downstream of rivers. The maximum value of SOM is 12 % in the first layer, while 8.3 % of SOC in the first layer. Nevertheless, the value of SOC decrease in the near future, it is as indication Barito Delta contribute to carbon stock loss realizing to atmosphere that can rise greenhouse gasses and climate change.